2006
DOI: 10.1007/s10452-004-0189-8
|View full text |Cite
|
Sign up to set email alerts
|

Erodibility and erosion patterns of mudflat sediments investigated using an annular flume

Abstract: Laboratory flume experiments were carried out, to measure the effect of biota on erodibility of mudflat sediments. The experiments sought to reproduce the environment of the lower mudflat at Hythe, Southampton Water, Southern England; this is characterised by fine grain-size and a surface layer of very fluid mud. Natural sediments were used to produce settled beds in the Lab Carousel, an annular flume of 2 m diameter. The following bed conditions were investigated diatom biofilms; the addition of cockles (Cera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 20 publications
2
22
0
Order By: Relevance
“…7). Overall, our results suggest that cockles facilitated young generations by increasing sediment stability at the sandy sites and by alleviating the effects of organic enrichment at the mussel bed sites, thus acting as both sediment stabilizators (Andersen et al, 2010;Donadi et al, 2013b) and bioturbators (Flach, 1996;Montserrat et al, 2009;Neumeier et al, 2006).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…7). Overall, our results suggest that cockles facilitated young generations by increasing sediment stability at the sandy sites and by alleviating the effects of organic enrichment at the mussel bed sites, thus acting as both sediment stabilizators (Andersen et al, 2010;Donadi et al, 2013b) and bioturbators (Flach, 1996;Montserrat et al, 2009;Neumeier et al, 2006).…”
Section: Discussionmentioning
confidence: 88%
“…Cockles live in the upper few cm of the sediment and can occur in dense assemblages of many thousands m −2 (Jensen, 1992). Although several studies emphasized the bioturbating effects of cockles (Flach, 1996;Neumeier et al, 2006), high densities of cockles can also increase sediment stability through the production of mucus-rich biodeposits and facilitation of sedimentbinding diatom colonies (Ciutat et al, 2007;Donadi et al, 2013b). Sediment stabilization may affect cockle recruitment and post-larval processes (Bouma et al, 2001;Kater et al, 2006;Piersma et al, 2001), for instance by enhancing the ability of juvenile bivalves to anchor themselves to the substrate, thereby buffering negative effects of waves and currents (Armonies, 1996;Armonies and Hellwig-Armonies, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Da S. Quaresma et al (2007) found that shell and shell hash was transported landward by waves as bedload over an intertidal flat and was so abundant that it formed extensive cheniers. Neumeier et al (2006) found that live cockles locally weakened the bed through bioturbation and acted as large roughness elements on the bed, causing disturbance of the flow, so that the effective critical shear stress was reduced up to a factor of two. The density of cockles in their experiments was so low that the surface was far from covered entirely by dead shells.…”
Section: Discussionmentioning
confidence: 98%
“…Seasonal changes in the sediment bed due to biological effects are also neglected in the present model. Yet, the formation of a biofilm in spring by diatoms (Holland et al 1974;Yallop et al 1994) may cause a temporal increase in τ crit in spring and summer by up to a factor 5 (Neumeier et al 2006;Le Hir et al 2007). Test runs with our model, implementing the (de)stabilising influence of benthos on mud as proposed by Borsje et al (2008) showed that this had a significant effect on bed composition, but the amount of mud stored or released in this way was too small (at least in the model) to influence mud concentration in the water column on the scale of the whole estuary (van Kessel et al 2007).…”
Section: Discussionmentioning
confidence: 99%